Anti-AMPA-Receptor Encephalitis Presenting as a Rapid-Cycling Bipolar Disorder in a Young Woman with Turner Syndrome - Quaranta, Giuseppe; Maremmani, Angelo Giovanni Icro; Perugi, Giulio (Case Reports in Psychiatry, 2015)
Background. Autoimmune encephalitis is a disorder characterised by the subacute onset of seizures, short-term memory loss, and psychiatric and behavioural symptoms. Initially, it was recognised as a paraneoplastic disorder, but recently a subgroup of patients without systemic cancer was identified. Case Description. We describe a 20-year-old woman with Turner syndrome presenting with a treatment-resistant rapid cycling bipolar disorder with cognitive impairment. She was diagnosed with anti-AMPA-receptor encephalitis. She showed marked improvement after starting memantine and valproic acid. Conclusion. This case description emphasises the importance of timely recognition of autoimmune limbic encephalitis in patients with psychiatric manifestations and a possible predisposition to autoimmune conditions, in order to rule out malignancy and to quickly initiate treatment.